ON THE PROBLEM OF CLASSIFICATION OF BATTLE TOWERS OF INGUSHETIA - Sampiev, Israpil Magometovic (History, Archeology and Ethnography of the Caucasus, 2023)
The relevance of the problem under consideration, in addition to its epistemological interest, is also due to its practical significance. A large number of medieval archaeological and historical monuments of mountainous Ingushetia are disappearing, being destroyed before our eyes, and are in a dilapidated state. The state, having declared these objects of cultural heritage of the Ingush as its property, cares little about their preservation, practically does not allocate funds for their conservation and, moreover, restoration. Local teip communities are invited to finance these works themselves. However, even isolated cases of restoration work at the expense of sponsors cause a lot of disputes and questions. In particular, one of such pressing issues is the question of the restoration of combat towers according to one or another of their type, since they differ in their structural details, especially in their roofing part, which is most susceptible to destruction. Such controversial situations arose, for example, during the recent restoration of combat towers in the villages of Harp and Bisht of the Jeyrakh district of the Republic of Ingushetia. This problematic situation seems to be based on the imperfection of the existing classifications of Ingush combat towers. The purpose of the article is a critical analysis of the basic principles (bases) of the classification of combat towers and an assessment of their suitability for the reconstruction of the appearance of the latter. To achieve this goal, it is supposed to analyze and compare the classifications available in the literature (including types and types of combat towers and their distinctive features), identify their weaknesses and strengths, as well as assess the suitability of existing classifications as a possible scientific and theoretical basis for the restoration of Ingush combat towers. As a methodological basis for the research, this article uses a comparative analysis of the main classifications of Ingush combat towers, identification of possible classification principles and their assessment with the so-called suitability for the purposes of reconstruction of the appearance of the roofs of combat towers, as well as content analysis of the literary register of medieval tower structures of Ingushetia.